Diversity and continuity in the pottery traditions of the Wallacean islands: New evidence from Makpan Cave, Alor island, Indonesia. (March 2023) - Beaumont, Phillip; Leclerc, Mathieu; Kealy, Shimona; O'Connor, Sue
Abstract: This study examines a pottery assemblage from Makpan Cave, Alor, Indonesia dating from ∼3300 BP to historic times, constituting one of only a few documented ceramic studies from the Nusa Tenggara Timur archipelago. The assemblage is characterised by idiosyncratic decorative features along with a range of surface finishes not commonly emphasised in other research in the region. The Makpan pottery exhibits a notable consistency over time suggesting an enduring and stable pottery tradition, yet petrographic examination reveals a number of manufacturing locations with the possibility of offshore imports. The study also reports on the occurrence of baked clay, mostly concentrated in levels dating to around 11, 500 BP. Finds of baked clay in Island Southeast Asia are little known with only one other major documented example and its use and purpose at Makpan is currently enigmatic. A long history of inter-island communications and contact is highlighted as the key factor in bringing new technologies, including Neolithic pottery, to Makpan and throughout the region. Although Austronesian speakers are conventionally credited with introducing ceramics throughout ISEA, the Makpan case study indicates that a variety of peoples may have participated in the dispersal of pottery into southern Wallacea.